Biomechanical comparison of anterior cervical corpectomy and fusion, anterior controllable antedisplacement and fusion, and anterior cervical X-shape-corpectomy and fusion in the surgical treatment of ossification of the posterior longitudinal ligament: a finite element analysis - Lian, Xiong-Han; Xue, Huo-Huo; Sun, Wen-Jia; Chen, Yu-Fan; Zeng, Zhi-Feng; Chen, Liang; Xue, Jing-Lai (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAnterior Cervical Corpectomy and Fusion (ACCF), Anterior Controllable Antedisplacement and Fusion (ACAF), and Anterior Cervical X-Shape-Corpectomy and Fusion (ACXF) have been shown to achieve similar decompression outcomes in the treatment of ossification of the posterior longitudinal ligament. However, the potential biomechanical differences remain unclear.MethodsFinite element models of the cervical spine (C3-C7) were constructed to simulate ACCF, ACAF, and ACXF. Compare the ranges of motion (ROMs), von Mises stresses in the fixation systems and cortical endplates, and adjacent intervertebral disc pressures (IDPs) under loading conditions.ResultsPostoperatively, ROMs in the fusion area were significantly restricted, with ACAF exhibiting the most severe, followed by ACCF, while ACXF showed the lightest. Peak stresses in the internal fixation systems were highest in ACCF, particularly within the fusion devices. The cages in ACAF experienced lower stress than those in ACXF, whereas the screws showed the opposite trend. ACCF had the highest cortical endplate stresses, while ACXF had the lowest adjacent IDPs.ConclusionACAF and ACXF demonstrate superior biomechanical properties in terms of stability, reduced internal fixation system risk, resistance to subsidence, and lower incidence of adjacent segment disease. As a result, they may serve as viable alternatives to ACCF in certain cases.